2017
DOI: 10.1155/2017/6809745
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Adiponectin in Endothelial Progenitor Cells Protects a Rat Model of Cerebral Ischemia

Abstract: Endothelial progenitor cells (EPCs), as precursors to endothelial cells, play a significant part in the process of endogenous blood vessel repair and maintenance of endothelial integrity. Adiponectin (APN) is an adipocyte-specific adipocytokine. In this study, we aim to test whether we transplant a combined graft of EPCs transfected with the adiponectin gene into a rat model of cerebral ischemia could improve functional recovery after middle cerebral artery occlusion (MCAO). Sprague-Dawley (SD) rats were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
(33 reference statements)
2
19
0
1
Order By: Relevance
“…Changing the media every 72 hours and the growth state of the cells were observed every day. In our previous experiments [27], we identified these cells by the property of uptaking acetylated LDL (ac-LDL) and Ulex europaeus agglutinin-1 (UEA-1) by EPCs, and cells cultured by this method have been identified as EPCs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Changing the media every 72 hours and the growth state of the cells were observed every day. In our previous experiments [27], we identified these cells by the property of uptaking acetylated LDL (ac-LDL) and Ulex europaeus agglutinin-1 (UEA-1) by EPCs, and cells cultured by this method have been identified as EPCs.…”
Section: Methodsmentioning
confidence: 99%
“…72 h after transfection, the cells were placed under an inverted fluorescence microscope to observe the expression of enhanced green fluorescent protein (EGFP) and evaluate the results of transfection, and the transfection rate was calculated according to the following formula: transfection rate = positive cells/total cells per field × 100%. The expression of APN from APN-EPCs and EPCs were detected by Western blot analysis [27].…”
Section: Gene Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that genetically-transplanted endothelial progenitor cells with adiponectin by lentivirus could reduce cerebral infarction volume, improve behavior outcome, increase microvessel density, and reduce cell apoptosis [33] .…”
Section: Apn-gene Modified Cell Therapy Alleviates Cerebral Ischemic mentioning
confidence: 99%